The Role of Cone Beam Computed Tomography in Dental Practice: An Endodontic Case Report - Monica Monea; Kovacs Monika; Nicoleta Suciu; Pop Mihai (European Scientific Journal, ESJ, 2016)
We aim to present a case of obliterated root canal which was successfully treated in our dental faculty using these new techniques. Teeth with calcified root canals referred for endodontic treatment pose pa rticular diagnostic and treatment challenges. Usually these are intact traumatized anterior teeth without symptoms except of slight discoloration, without apical radiolucency. The thorough knowledge of endodontic anatomy and the use of modern equipment as the cone beam computed tomography (CBCT) and operating microscope are the basis for long term clinical and radiological success of these cases. The use of rotary endodontic instrumentation in conjunction with chelating agents as EDTA have been advocated for the endodontic instrumentation of narrow or obliterated root canals, where the apical dentin is usually more mineralized. CBCT images offered superior information in comparison to conventional radiographs but it must be taken into consideration only for difficult cases, due to higher radiation dose and costs.